Collision-induced stimulated photon echo generated at transition 0–1 on broad spectral line conditions. (22nd February 2018) - Rubtsova, N N; Gol'dort, V G; Ishchenko, V N; Khvorostov, E B; Kochubei, S A; Borisov, G M; Ledovskikh, D V; Reshetov, V A
Abstract: For the first time, the collision induced stimulated photon echo generated at transition 1 S 0 → 3 P1 of 174 Yb (type 0–1) in the mixture of gases Yb  +  Xe was investigated in the presence of weak longitudinal magnetic field, with experimental parameters corresponding to broad spectral line conditions. Comparison of the experimental echo amplitude versus magnetic field strength dependence with the theoretical curve shows a very good agreement, giving rise to an improved estimate for the difference between alignment and orientation decay rates.